FAME: Fast Attribute-based Message Encryption - Chase, Melissa; Agrawal, Shashank (CCS '17 Proceedings of the 2017 ACM SIGSAC Conference on Computer and Communications Security, 2017)
Time and again, attribute-based encryption has been shown to be the natural cryptographic tool for building various types of conditional access systems with far-reaching applications, but the deployment of such systems has been very slow. A central issue is the lack of an encryption scheme that can operate on sensitive data very efficiently and, at the same time, provides features that are important in practice. This paper proposes the first fully secure ciphertext-policy and key-policy ABE schemes based on a standard assumption on Type-III pairing groups, which do not put any restriction on policy type or attributes. We implement our schemes along with several other prominent ones using the Charm library, and demonstrate that they perform better on almost all parameters of interest.